The stock markets, banks and growth Nexus: Asian Islamic countries - Rajabi, Ehsan; Muhammad, Junaina (Wiley, 2014)
This paper is primarily concerned with the empirical relationship between the stock market and banking developments and economic growth in a panel of 10 Asian Islamic countries over the period 1990–2009. In order to explore whether there is a positive relationship between the financial development and growth, this study employs the dynamic panel pooled mean-group techniques. Having controlled the simultaneity bias, the obtained results prove that the development of both banks and stock markets exerts a significant effect on the economic growth. Furthermore, the results also indicated that in the long run, the bank credit, the turnover ratio, as well as the government consumption variables would be significant while positively contributing to the economic growth. Nonetheless, it was observed that not always the sign of the relationship was identical among diverse specifications and proxies. More specifically when controlling the Asian financial crisis, the stock market development exerts a negative effect on the growth, although it is negative for the banking development. It needs to be asserted that the findings obtained in this research are in accordance with the theories which lay emphasis on the significant and positive role of the financial development in the process of economic growth.